Analysis of Teaching Readiness of Students of STAIN Mandailing Natal at MAN 1 Mandailing Natal - Ikman Baktarudin; Rosdiana Safitri; Wulan Lubis; Syamsiah Depalina Siregar (STKIP Pesisir Selatan, 2026)
The purpose of this study was to evaluate the teaching preparation of students participating in the Islamic Religious Education and English Education Field Experience Program at MAN 1 Mandailing Natal. The success of the learning process depends on teacher preparation; this preparation includes planning learning materials, mastery of the material, method selection, and the mental and pedagogical readiness of the student interns. This study used qualitative and descriptive methodologies. PPL students, supervising teachers, and school officials were observed, interviewed, and documented to collect data. The results showed that the PPL students of the Islamic Religious Education and English Education Programs were well prepared to teach, especially in creating lesson modules and mastering the material. However, several obstacles remained. These included limited teacher experience, classroom management, and adapting learning methods to student characteristics. As a result, supervising lecturers and mentor teachers require more intensive guidance and mentoring to ensure the quality of preparation and implementation of PPL students' learning improves.